PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE (TPS) BERBASIS PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR BAHASA INDONESIA DI KELAS V SDN 15 NANGA PINOH - Sukarni, Ade; Putri, Rizky Oktora Prihadini Eka; Fitriana, Dina (STKIP Melawi, 2016)
Abstract: This study aims to find out the result of learning Indonesian language of the students in fifth grade at Public Elementary School Number 15 Nanga Pinoh using a cooperative model of Think-Pair-Share (TPS) based on a scientific approach. This research method used quantitative research, and the type of the research is quasi experimental research (Quasi Experiment Design) in the form of Noneequavalent Control Group Design. The result of the research showed that the pre-test value in experiment and control class is tcount = -0.854 <ttable = 2.045. This means that there is not any differences found, whereas in the post-test value in the experimental class and the control tcount = 3.180>ttable = 2.045 for α 5% = 0.05 showed a difference between post-test experiment with control, therefore there is a significant difference between the learning model experiments andthe conventional methods which was applied on students in class VA and VB at Public Elementary School Number 15 Nanga Pinoh.Keywords:application of think pair share (tps), scientific approach, result of learningindonesian language. Abstrak: Penelitian ini bertujuan mengetahui hasil belajar Bahasa Indonesia siswa kelas V SDN 15 Nanga Pinoh menggunakan model kooperatif Think-Pair-Share (TPS) berbasis pendekatan saintifik. Metode penelitian ini menggunakan penelitian kuantitatif, jenis penelitian ini adalah penelitian eksperimen semu atau (Quasi Exsperimen Design) bentuk Noneequavalent Control Group Design. Hasil penelitian diperoleh nilai pre-test pada kelas eksperimen dan kontrol yaitu thitung = -0.854 <ttabel = 2.045. Berarti tidak terdapat perbedaan, sedangkan pada nilai post-test di kelas eksperimen dan kontrol thitung = 3.180 >ttabel = 2.045 untuk α 5%=0,05 berarti terdapat perbedaan antara post-tes eksperimen dengan kontrol, sehingga terdapat perbedaan yang signifikan antara model pembelajaran eksperimen dengan metode konvensional pada kelas VA dan VB SDN 15 Nanga Pinoh.Kata Kunci: penerapan think pair share (tps), pendekatan saintifik, hasil belajar bahasa indonesia.